Multiscale and multimodal X-ray analysis: Quantifying phase orientation and morphology of mineralized turkey leg tendons. (15th July 2021) - Maurya, Anjani K.; Parrilli, Annapaola; Kochetkova, Tatiana; Schwiedrzik, Jakob; Dommann, Alex; Neels, Antonia
Abstract: Fibrous biocomposites like bone and tendons exhibit a hierarchical arrangement of their components ranging from the macroscale down to the molecular level. The multiscale complex morphology, together with the correlated orientation of their constituents, contributes significantly to the outstanding mechanical properties of these biomaterials. In this study, a systematic road map is provided to quantify the hierarchical structure of a mineralized turkey leg tendon (MTLT) in a holistic multiscale evaluation by combining micro-Computed Tomography (micro-CT), small-angle X-ray scattering (SAXS), and wide-angle X-ray diffraction (WAXD). We quantify the interplay of the main MTLT components with respect to highly ordered organic parts such as fibrous collagen integrating inorganic components like hydroxyapatite (HA). The microscale fibrous morphology revealing different types of porous features and their orientation was quantified based on micro-CT investigations. The quantitative analysis of the alignment of collagen fibrils and HA crystallites was established from the streak-like signal in SAXS using the Ruland approach and the broadening of azimuthal profiles of the small and wide-angle diffraction peaks. It has been in general agreement that HA crystallites are co-aligned with the nanostructure of mineralized tissue. However, we observe relatively lower degree of orientation of HA crystallites compared to the collagen fibrils, which supports the recent findings of the structural interrelations within mineralized tissues. The generic multiscale characterization approach of this study is relevant to any hierarchically structured biomaterials or bioinspired materials from the μm-nm-Å scale. Hence, it gives the basis for future structure-property relationship investigations and simulations for a wide range of hierarchically structured materials. Statement of significance: Many fibrous biocomposites such as tendon, bone, and wood possess multiscale hierarchical structures, responsible for their exceptional mechanical properties. In this study, the 3-dimensional hierarchical structure, the degree of orientation and composition of mineralized tendon extracted from a turkey leg were quantified using a multimodal X-ray based approach combining small-angle X-ray scattering and wide-angle X-ray diffraction with micro-Computed Tomography. We demonstrate that hydroxyapatite (HA) domains are co-aligned with the nanostructure of mineralized tissue. However, the lower degree of orientation of HA crystallites was observed when compared to the collagen fibrils. The generic multiscale characterization approach of this study is relevant to any hierarchically structured biomaterials or bioinspired materials from the micrometer over the nanometer to the Angström scale level. Graphical abstract: Image, graphical abstract